Relación entre vida y espíritu en la antropología de Maz Scheler - Suances Marcos, Manuel (ENDOXA, 2002)
The anthropological dualism soul-body, arising from Platonism and which culminates in Descartes, is elaborated by Max Scheler, in a new understanding ofthe concepts of life and spirit respectively. The German philosopher emphasizes the interdependence of both realities, despite their dijferent natures, with in the structural order of the human being. This interdependence has degrees of movement according to the thought process of Scheler. It is important to see that both realities gradually unite with in a wide range of perspectives-metaphysical, gnosiological, axiological, psychological and cultural.